Penyuluhan Hukum Terkait Penyalahgunaan Narkoba Kepada Anak Remaja Daerah Cimindi Dan Sekitar Alun-Alun Kota Bandung - Sundari, Nata; Fadil Mutaqin; Shinta Pramudita Diah Pitaloka; Bentar Samudra Nusantara; Muhammmad Galih Irfansyah (Pusat Riset dan Inovasi Nasional, 2023)
In adolescence vulnerable to the influence of drugs. In these adolescents drugs can be introduced through association. Teenagers are also in a phase of searching for identity where they are curious. At this time they also began to be less supervised by their parents. This is because drugs have an unfavorable impact on mental and physical health as well as adolescents where teenagers are still of school age. so it is very important to conduct legal counseling regarding drug abuse to adolescents. So it is necessary to know the meaning of drugs, types of drugs, routes of drug use, the basic laws of drug abuse, and what are examples of drug abuse. The teaching method uses the focuser method, brainstorming, ranking exercises, group discussion forums, critical thinking, question and answer. The purpose of this writing is to find out how the law regarding drug counseling to teenagers in Cimindi. Apart from that, it is also to add insight to teenagers and so that teenagers can convey it back to the people around them. So that legal counseling can be useful for many people. So that legal counseling regarding narcotics can be a preventive measure to deal with drug cases in adolescents. This legal counseling activity was carried out for Cimindi youth, especially for hangout youth, youth organizations, and futsal children.